Trophic niche differentiation and foraging plasticity of long-finned pilot whales (Globicephala melas edwardii) in Tasmanian waters: insights from isotopic analysis - Christine H. Jackson; Rosemary Gales; Yves Cherel; George D. Jackson; Patti Virtue; Patti Virtue (Frontiers in Marine Science)
Understanding the foraging preference of cetaceans is crucial for assessing their role as apex predators and indicators of marine ecosystem health. Using stable isotope analysis, we investigated trophic niche differentiation and foraging plasticity in 141 long-finned pilot whales (Globicephala melas edwardii) that stranded along the Tasmanian coast at three locations (Marion Bay, King Island, and Maria Island). Stranding location accounted for most of the variability in skin isotopic values (δ13C: - 17.9 ± 0.2 ‰ to –16.9 ± 0.2 ‰, Principal Coordinate 1 = 89%), likely reflecting differences in foraging habitats. In addition, isotopic niche overlap ranged from minimal (0-10% between Marion Bay and Maria Island) to moderate (between Marion Bay and King Island, and King Island and Maria Island). While sex related differences in isotopic niche space were minimal overall, there was some variability in the core niche space between males and females at Maria Island. Dietary proportions from our mixing model support a predominantly cephalopod diet for pilot whales in Tasmanian waters (91%, CI: 63-90%), with greater contributions from offshore dietary sources (68%, CI: 25-95%). The dietary variability across the three strandings highlights the foraging plasticity of pilot whales, which despite their preferences for a wide range of oceanic cephalopods, can adopt a more generalist feeding strategy when necessary. These findings provide valuable insights into the ecological role and adaptability of pilot whales in Tasmanian waters, highlighting the importance of monitoring apex predators to inform conservation and ecosystem management strategies in dynamic marine ecosystems.